Canine and feline in situ mammary carcinoma: A comparative review. Issue 6 (November 2022) - Burrai, Giovanni P.; Baldassarre, Valeria; Brunetti, Barbara; Iussich, Selina; Maniscalco, Lorella; Mariotti, Francesca; Sfacteria, Alessandra; Cocumelli, Cristiano; Grieco, Valeria; Millanta, Francesca; Paciello, Orlando; Papparella, Serenella; et al.
Carcinoma in situ of the breast is a well-known entity in humans. In veterinary medicine, particularly in canine and feline mammary literature, there is no agreement whether the term in situ should be used to indicate a specific carcinoma histotype or the noninvasive status of a carcinoma of any histotype. Moreover, in the most recent histologic classification of mammary tumors published by the Davis-Thompson Foundation, it is suggested to abandon the term carcinoma in situ given the lack of standardized criteria defining this entity, replacing it with epitheliosis or ductal/lobular hyperplasia with severe atypia. This publication presents a critical review of the term in situ in human and veterinary medicine considering the evolution of the term over the years and its heterogeneous use by different authors, including variations in immunohistochemical markers for classification. This review aims to point out the lack of uniformity in the nomenclature and classification issues in veterinary medicine regarding the use of the term in situ, laying the ground for a process of standardization in future publications.